Multi-Omics Approach Reveals the Potential Core Vaccine Targets for the Emerging Foodborne Pathogen Campylobacter jejuni - Cao, Hengchun; Xu, Hanxiao; Ning, Chunhui; Xiang, Li; Ren, Qiufang; Zhang, Tiantian; Zhang, Yusen; Gao, Rui (Frontiers in Microbiology, 2021)
Campylobacter jejuni is a leading cause of bacterial gastroenteritis in humans around the world. The emergence of bacterial resistance is becoming more serious, and therefore, development of new vaccines is considered to be an alternative strategy to against the drug-resistant pathogen. In this study, we investigated the pangenome of 173 C. jejuni strains, and analyzed the phylogenesis and virulence factor genes. In order to acquire a high-quality pangenome, the genomic relatedness was firstly performed with the average nucleotide identity analyses, and an open pangenome of 8,041 gene families was obtained with correct taxonomy genomes. Subsequently, virulence property of the core genome was analyzed and 145 core virulence factor (VF) genes were obtained. Upon proteomics and immunological analyses, five core VF proteins with high antigenicity were selected as the potential core vaccine targets. Further, functional annotations indicated that these proteins are involved in important molecular functions and biological processes, such as adhesion, regulation and secretion. In addition, transcriptome analysis in human cells and pig intestinal loop proved that these vaccine target genes are important in the virulence of C. jejuni in different hosts. Comprehensive pangenome and relevant animal experiments will facilitate discovering the potential core vaccine targets with improved efficiency in reverse vaccinology. Likewise, this study provided some insights into the genetic polymorphism and phylogeny of C. jejuni and discovered the potential vaccine candidates. Prospective development of new vaccines using the targets will be an alternative to use of antibiotics and prevent the development of multi-drug resistant C. jejuni.